PJMHS 2021
DOI: 10.53350/pjmhs211572374
|View full text |Cite
|
Sign up to set email alerts
|

A Cross -Ectional Survey on Knowledge, Attitude and Practices of Physical Therapists Towards Covid-19 Pandemic

Abstract: Objectives: The purpose of this study was to determine the number of physiotherapists who interrupted their services because of the COVID-19 pandemic and to verify the procedures adopted by the physiotherapists who are still working. Methods: It was a Cross sectional study. Study Setting was University of South Asia, Lahore. Data was collected through self-administered questionnaire. Physiotherapists working in Government and Private Hospitals in Lahore were recruited. Data was collected from October 2020 to N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Several studies were conducted to assess the knowledge and attitude of physiotherapists about COVID-19; these were conducted regarding the source of awareness, clinical symptoms, diagnostic measures, mode of transmission, risk mitigation, and preventive measures. Tese studies found that physiotherapists are sufciently knowledgeable about COVID-19 [21][22][23][24]. However, these studies had not assessed (i) the knowledge and attitude of physiotherapists, specifcally in those who worked in COVID-19 ICUs, and (ii) awareness of gold standard rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies were conducted to assess the knowledge and attitude of physiotherapists about COVID-19; these were conducted regarding the source of awareness, clinical symptoms, diagnostic measures, mode of transmission, risk mitigation, and preventive measures. Tese studies found that physiotherapists are sufciently knowledgeable about COVID-19 [21][22][23][24]. However, these studies had not assessed (i) the knowledge and attitude of physiotherapists, specifcally in those who worked in COVID-19 ICUs, and (ii) awareness of gold standard rehabilitation protocols.…”
Section: Discussionmentioning
confidence: 99%